2021
DOI: 10.3390/ijms222111324
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Annotated Long Noncoding RNAs Associated with Ischemia in the Human Heart

Abstract: Background: Long noncoding RNAs (lncRNAs) have been implicated in the pathogenesis of cardiovascular diseases. We aimed to identify novel lncRNAs associated with the early response to ischemia in the heart. Methods and Results: RNA sequencing data gathered from 81 paired left ventricle samples from patients undergoing cardiopulmonary bypass was collected before and after a period of ischemia. Novel lncRNAs were validated with Oxford Nanopore Technologies long-read sequencing. Gene modules associated with an ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…For expression estimation and transcript-level expression profiling, StringTie was then utilized in conjunction with GENCODE v25 ( https://www.gencodegenes.org/mouse/ ) as the reference annotation file. Subsequently, a set of inclusion criteria was applied to the transcripts obtained from the output GTF file ( Ounzain et al, 2015 ; Azlan et al, 2019 ; Ward et al, 2021 ). The criteria were as follows: (i) the transcripts should be multi-exonic; (ii) they should correspond to gffcompare v0.11.2 ( Pertea and Pertea, 2020 ) class codes ‘u' (intergenic), ‘i' (intronic), ‘x' (antisense), or ‘y' (containing a reference gene within its intron) based on the reference annotation GENCODE v25 ( Ward et al, 2021 ); (iii) the transcript length should exceed 200 nucleotides; (iv) the transcripts should align to the autosomes or the X chromosome; (v) they should lack coding potential and possess an open reading frame (ORF) shorter than 300, as assessed by the Coding Potential Assessment Tool (CPAT v3.0) ( Clark et al, 2015 ; Chen et al, 2016 ) using default settings,; (vi) transcripts identified as coding regions by TransDecoder v5.5 ( https://github.com/TransDecoder/TransDecoder ) and those with homology to the UniProt dataset determined by BLASTP were discarded; (vii) transcripts with significant hits for known protein domains, identified using HMMER against the Pfam database ( Finn et al, 2014 ), were also discarded; and (viii) transcripts with a read count less than 5 across all samples were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…For expression estimation and transcript-level expression profiling, StringTie was then utilized in conjunction with GENCODE v25 ( https://www.gencodegenes.org/mouse/ ) as the reference annotation file. Subsequently, a set of inclusion criteria was applied to the transcripts obtained from the output GTF file ( Ounzain et al, 2015 ; Azlan et al, 2019 ; Ward et al, 2021 ). The criteria were as follows: (i) the transcripts should be multi-exonic; (ii) they should correspond to gffcompare v0.11.2 ( Pertea and Pertea, 2020 ) class codes ‘u' (intergenic), ‘i' (intronic), ‘x' (antisense), or ‘y' (containing a reference gene within its intron) based on the reference annotation GENCODE v25 ( Ward et al, 2021 ); (iii) the transcript length should exceed 200 nucleotides; (iv) the transcripts should align to the autosomes or the X chromosome; (v) they should lack coding potential and possess an open reading frame (ORF) shorter than 300, as assessed by the Coding Potential Assessment Tool (CPAT v3.0) ( Clark et al, 2015 ; Chen et al, 2016 ) using default settings,; (vi) transcripts identified as coding regions by TransDecoder v5.5 ( https://github.com/TransDecoder/TransDecoder ) and those with homology to the UniProt dataset determined by BLASTP were discarded; (vii) transcripts with significant hits for known protein domains, identified using HMMER against the Pfam database ( Finn et al, 2014 ), were also discarded; and (viii) transcripts with a read count less than 5 across all samples were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The bioinformatics pipeline was designed to detect mRNAs, lncRNAs and circRNAs and generate data on putative novel lncRNA and circRNA transcripts (summarised in Supplementary Figure S2 ) [ 29 ]. The pipeline is freely available to download at , accessed on 20 August 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Besides its role in tumor progression, recent studies reveal that RSUME is connected with cardiac tissue response to ischemia and stroke ( 18 , 19 ) ( Figure 2 ). Enhanced SUMOylation has been proposed to protect from stroke and ischemia of the brain ( 20 , 21 ).…”
Section: Rsume Expression In Pathological Tissue Responsesmentioning
confidence: 99%
“…Ward et al. carried out a detailed study in which the comparison of ventricular tissue after and before ischemia in humans shows that several long non-coding RNAs (lncRNAs) are differentially expressed and related to fast response to ventricular ischemia ( 18 ). From the novel lncRNA group, a particular lncRNA targets five regulatory loci (expression quantitative trait loci, eQTL) for RSUME, and consequently, this lncRNA’s expression correlates with RSUME expression in this study group ( 18 ).…”
Section: Rsume As a Biomodulator In Developmentmentioning
confidence: 99%